2023
DOI: 10.1111/1541-4337.13115
|View full text |Cite
|
Sign up to set email alerts
|

α‐Dicarbonyl compounds in food products: Comprehensively understanding their occurrence, analysis, and control

Abstract: α-Dicarbonyl compounds (α-DCs) are readily produced during the heating and storage of foods, mainly through the Maillard reaction, caramelization, lipidperoxidation, and enzymatic reaction. They contribute to both the organoleptic properties (i.e., aroma, taste, and color) and deterioration of foods and are potential indicators of food quality. α-DCs are also important precursors to hazardous substances, such as acrylamide, furan, advanced lipoxidation end products, and advanced glycation end products, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 233 publications
0
7
0
Order By: Relevance
“…Thr-ARP rapidly went through 1,2-enolization or 2,3-enolization after being heated to form 3-DX or 1-DX, respectively, while at the same time, regenerated threonine was released. When the reaction solution was acidic or neutral, the main path of Thr-ARP degradation was to form 3-DX through 1,2-enolization, , and the results of this research (pH ≤ 7) showed that no 1-DX was generated. Generally, some generated 3-DX then went through retro-aldolization to produce active α-dicarbonyl compounds, such as glyoxal and methylglyoxal .…”
Section: Resultsmentioning
confidence: 99%
“…Thr-ARP rapidly went through 1,2-enolization or 2,3-enolization after being heated to form 3-DX or 1-DX, respectively, while at the same time, regenerated threonine was released. When the reaction solution was acidic or neutral, the main path of Thr-ARP degradation was to form 3-DX through 1,2-enolization, , and the results of this research (pH ≤ 7) showed that no 1-DX was generated. Generally, some generated 3-DX then went through retro-aldolization to produce active α-dicarbonyl compounds, such as glyoxal and methylglyoxal .…”
Section: Resultsmentioning
confidence: 99%
“…Products stored at room temperature (14-23), regardless of the packaging form, had higher salt contents (4.91-11.52%). The vacuum-packaged products (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) for frozen storage exhibited reduced salt content ranging from 0.12% to 1.78%, demonstrating an extended shelf life. It is advisable to avoid the frequent consumption of snack products and salted fish products that are stored at room temperature to reduce excessive sodium intake.…”
Section: Chemical Composition Of Commercially Prepared and Prefabrica...mentioning
confidence: 99%
“…(MGO), diacetyl (DA), and pentanedione (PD), and so on [1,2]. α-DCs are mainly produced during food heating treatment containing frying and baking [3][4][5]. In the heating process, α-DCs formed through Maillard reaction, oxidation reaction, and glycolysis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…α‐Dicarbonyl compounds (α‐DCs) are a series of highly reactive intermediates, such as d ‐glucosone (DS), 3‐deoxyglucosone (3‐DG), glyoxal (GO), methylglyoxal (MGO), diacetyl (DA), and pentanedione (PD), and so on [1, 2]. α‐DCs are mainly produced during food heating treatment containing frying and baking [3–5]. In the heating process, α‐DCs formed through Maillard reaction, oxidation reaction, and glycolysis [6, 7].…”
Section: Introductionmentioning
confidence: 99%